2022
DOI: 10.3389/fnut.2021.823803
|View full text |Cite
|
Sign up to set email alerts
|

Preparation, Structural Features and in vitro Immunostimulatory Activity of a Glucomannan From Fresh Dendrobium catenatum Stems

Abstract: Dendrobium catenatum polysaccharides (DCPs) have attracted attention due to their multiple physiological activities and health benefits. In this study, a novel water-soluble DCP was obtained from fresh D. catenatum stems through three-phase partitioning and ethanol precipitation at room temperature. Its structural characteristics, rheological property, and in vitro immunostimulatory activity were evaluated. Results demonstrated that DCP was a homogenous polysaccharide with a carbohydrate content of 92.75% and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…Thus, DLP-1 and DLP-2 could be used as functional food additives (51). Similarly, DCP also has immunostimulatory activity in vitro, the mechanism of which was similar to that of DLP-1 and DLP-2 (53). Meanwhile, two component polysaccharides (DOP-1 and DOP-2) were isolated from D. officinale by DEAE cellulose and Sephacryl S-400, which caused a significant stimulation of cytokine secretion of both splenocytes and macrophages.…”
Section: Immunomodulatorymentioning
confidence: 78%
“…Thus, DLP-1 and DLP-2 could be used as functional food additives (51). Similarly, DCP also has immunostimulatory activity in vitro, the mechanism of which was similar to that of DLP-1 and DLP-2 (53). Meanwhile, two component polysaccharides (DOP-1 and DOP-2) were isolated from D. officinale by DEAE cellulose and Sephacryl S-400, which caused a significant stimulation of cytokine secretion of both splenocytes and macrophages.…”
Section: Immunomodulatorymentioning
confidence: 78%
“…Numerous studies have proved that polysaccharides from natural plants or other sources have a variety of properties, such as anti‐inflammatory, antioxidant, hypoglycemic, and immunostimulatory activities [9–13] . Among them, medicinal and edible substances are important sources of polysaccharides, which were proved to possess significant biological activities.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have proved that polysaccharides from natural plants or other sources have a variety of properties, such as anti-inflammatory, antioxidant, hypoglycemic, and immunostimulatory activities. [9][10][11][12][13] Among them, medicinal and edible substances are important sources of polysaccharides, which were proved to possess significant biological activities. It has been reported that the polysaccharide from Prunella vulgaris can promote the apoptosis of orbital fibroblasts and suppress the production of pro-inflammatory cytokines (NO, TNF-α, and IL-6) in RAW 264.7 cells.…”
Section: Introductionmentioning
confidence: 99%
“…GMs have a main chain of β-(1,4)-linked d -glucopyranosyl and β-(1,4)-linked d -mannopyranosyl backbone sometimes with a α-(1,6)-linked d -galactose side chain ( Korolenko et al, 2019 ). These NSPs have excellent immuno-enhancing, anti-tumor, hepatoprotective, cardioprotective, and antioxidant activity ( Liu et al, 2022 , Wang et al, 2022 ). Particularly, mannose, one of the degradation products of GMs, is taken up by the same transporter(s) as glucose but slows growth in several tumor types in vitro and in vivo ( Gonzalez et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%